Prevalence and Risk Factor Assessment of Peste des petits ruminants in Goats in Rajshahi, Bangladesh - Subir Sarker; Md.Hemayeatul Islam (Veterinary World, 2011)
The study was carried out to investigate the prevalence of Peste des petitis ruminants (PPR) in goats in Rajshahi District of Bangladesh, and its relation to age, sex, breeds and seasonal influence. In total, 627 goats were examined where 305 were males and 322 were females. The overall prevalence of PPR in goats was found to be 20.57% (n=129). From the various risk factors analysed, age categories of goats, sex, breed and seasonal influence were found to be significantly associated (p<0.01) with the prevalence of PPR. Findings suggested that the seasonal influence on outbreaks of this disease was significantly higher. The clinical prevalence of PPR was highest in the month of December (31.68%) and lowest in June (9.52%). The influence of sex on PPR outbreaks was found to be higher in male (28.52%) than female (13.04%) goats. As regards to age, PPR was significantly higher in young (31.06%) compared to sucklers (13.14%) and adult (10.15%). The susceptibility of Black Bengal goats to PPR was higher than other breeds. The results of this study showed that PPR is an important goat disease in the studied areas. Thus, an appropriate control strategy has to be designed and applied, which could involve prevention of contact with infected goats and vaccination against the PPR virus. [Vet. World 2011; 4(12.000): 546-549]